Studi Perbandingan Sistem Lisensi Kontraktor Konstruksi di Indonesia, Singapura, dan Malaysia - Giffary Otslan; Iris Mahani (Jurnal Teknik Sipil, 2025)
Abstract To ensure quality, public safety, competence and responsibility of construction,  every country implements a licensing system for construction contractors. In Indonesia, regulations on contractor licensing are regulated by the Construction Services Development Agency (LPJK), under the Ministry of Public Works and Housing (PUPR). Its primary objective is to ensure public safety by verifying that business entities possess adequate competence and accountability. This research aims to compares Indonesia's contractor licensing system with those of Malaysia and Singapore, identifying challenges such as limited understanding of licensing concepts, complex bureaucracy, and suboptimal implementation. Employing literature reviews, focus group discussions, and surveys, the research highlights best practices from Malaysia and Singapore—notably the single authority and single fee system—as models for reforming Indonesia's system. Using SWOT analysis, the study proposes strategic recommendations including certification requirement relaxation for business entity, enhanced information dissemination, and digital platform development. These reforms aim to improve Indonesia's licensing efficiency, support a healthy construction ecosystem, and enhance global competitiveness. Keywords: Comparative analysis, contractor licensing system, Indonesia, Malaysia, Singapore, strategic recommendations.